Morphological and Physio-biochemical Changes in Response to Foliar Application of Brassinosteroid and Water Stress in Apple Plants Under Pot Culture Study - Kumari, Sudarshna; Thakur, Anju (International Journal of Bio-resource and Stress Management, 2019)
The cultivated apple (Malus×domestica Borkh.), a member of family Rosaceae andsub-family Pomoideae, is native to South West Asia. The primary centre of origin of apple is thought to be the region, which includes the Asia Minor, the Caucasus, Soviet Central Asia and Himalayan India and Pakistan. Apple occupies a significant place in the horticultural wealth of Himachal Pradesh cultivated commercially in most countries in the temperate region of the world and in some tropical areas with high altitude.This study was undertaken to identify morphological and physio-biochemical changes in one-year-old grafted apple young seedling plants of two varieties of Super Chief and Red chief under 15 and 30 days of induced water stress followed by 0.05 ppm brassinosteroid and 0.1 ppm brassinosteroid. The maximum reduction in growth parameters was registered by plants subjected to 30 of water stress as compared to 15 days of water stress. Osmoregulating substances i.e. total free amino acid and total soluble sugars showed increased accumulation and enhanced activities of antioxidant enzyme catalase with increasing duration of water stress, which helped in enhancing drought tolerance. However, brassinosteroid at both concentrations could help in maintaining vital growth and biochemical processes under water stress conditions. Foliar spray of brassinosteroid (0.05 ppm) prior to imposition of stress can pave the way to minimize the deleterious effects of water stress on apple plants.